2016
DOI: 10.31478/201609u
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Development, Regulatory Review, and Use of Clinical Advances: A Vital Direction for Health and Health Care

Abstract: This publication is part of the National Academy of Medicine's Vital Directions for Health and Health Care Initiative, which called on more than 150 leading researchers, scientists, and policy makers from across the United States to assess and provide expert guidance on 19 priority issues for U.S. health policy. The views presented in this publication and others in the series are those of the authors and do not represent formal consensus positions of the NAM, the National Academies of Sciences, Engineering, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…The use of biomarkers has been encouraged by the FDA, which has now established means by which to qualify biomarkers for use in drug development, but there is a lack of validated biomarkers at this time 14, 15, 16. Commercial development and validation of biomarkers is slow, because development of robust and meaningful biomarkers is both time-consuming and extremely expensive (Figures 1 and 2) (17).…”
Section: Why Drugs Fail In Clinical Trialsmentioning
confidence: 99%
“…The use of biomarkers has been encouraged by the FDA, which has now established means by which to qualify biomarkers for use in drug development, but there is a lack of validated biomarkers at this time 14, 15, 16. Commercial development and validation of biomarkers is slow, because development of robust and meaningful biomarkers is both time-consuming and extremely expensive (Figures 1 and 2) (17).…”
Section: Why Drugs Fail In Clinical Trialsmentioning
confidence: 99%
“…More collaboration among the government, academia, and industry scientists will be necessary to advance innovation, including in the most challenging therapeutic areas such as autoimmune, neurodegenerative, and inflammatory diseases. 44 Exploration of multifocal public-private research partnerships has been the focus of initiatives at the NIH and FDA, including those related to the programs expanding brain and cancer research. Pharmaceutical and device companies are exploring sharing trial data in the interest of advancing very-large-scale clinical databases to facilitate discovery.…”
Section: Advance Science-forge Innovation-ready Clinical Research Pro...mentioning
confidence: 99%
“…Foster cross-disciplinary and public-private partnerships. More collaboration among the government, academia, and industry scientists will be necessary to advance innovation, including in the most challenging therapeutic areas such as autoimmune, neurodegenerative, and inflammatory diseases . Exploration of multifocal public-private research partnerships has been the focus of initiatives at the NIH and FDA, including those related to the programs expanding brain and cancer research.…”
Section: Essential Infrastructure Needsmentioning
confidence: 99%
“…Nonetheless, there are several underlying conditions which also suggest that the apparent regulatory delays are unintended. For instance, the upshot of the knowledge gap between innovators and reviewers is the additional time regulators may require in assessing and extending their understanding of the technology underpinning the NPI under review in order to arrive at a decision (Rosenblatt et al, 2016;Carpenter, 2004). This phenomenon is largely due to the pace at which technologies evolve as well as the complexity and sophistication they come with.…”
Section: Speed and Delaysmentioning
confidence: 99%
“…The ever-increasing numbers and complexity of data required for regulatory approval imposes a severe financial burden on innovating firms, and this is leading to the collapse of relatively smaller innovating firms in the pharmaceutical industry (Rosenblatt et al, 2016;Dimasi et al, 2003;Thomas, 1990). In recent times, several scholars have observed that in addition to loss in early entrant profit and competitive advantage that may be accrued to the innovating firm (Prieger, 2008;Carpenter, 2002), regulatory delay imposes high opportunity costs for investment, and research and development (R&D) time (DiMasi et al, 2010;Dimitri, 2010;Vernon et al, 2009;DiMasi, 2002).…”
Section: Cost and Uncertaintymentioning
confidence: 99%